Genotoxic and mutagenic effects of fipronil on mice - de Oliveira, Patricia Rosa [UNESP]; Bechara, Gervasio Henrique [UNESP]; Denardi, Sandra Eloisi [UNESP]; Oliveira, Rodrigo Juliano [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
The toxic effects of several compounds on ecosystems are not restricted to ecological disturbances, and may also affect long-term human health. Fipronil is highly efficient in the control of pests, including those resistant to pyrethroid, organophosphate, and carbamate insecticides. Relatively little is known about the action of fipronil in vertebrates. This study was aimed to evaluate the genotoxic and mutagenic potential of this compound in mice exposed to different doses and demonstrates the damage caused by fipronil on non-target organisms in artificial conditions. Mice were divided into five groups: group I = 30% of DL50 (15 mg/kg), group II = 50% of the DL50 (25 mg/kg), group III = DL50 (50 mg/kg), group IV = negative control, and group V = positive control. Peripheral blood was collected for the comet assay (24 h after exposure) and the micronucleus test (24,48 and 72 h after exposure). Our findings revealed that doses of 15 mg/kg (group I) and 25 mg/kg (group II) of fipronil did not have genotoxic or mutagenic effects. Only the highest dose tested (50 mg/kg) induced DNA damage 24 h after exposure, indicating the mutagenic potential of fipronil. Therefore, this or higher doses are not recommended, as they may be toxic to non-target organisms. (C) 2010 Elsevier GmbH. All rights reserved.
Keywords: Fipronil; Pesticide; Micronucleus; Comet; Mice